miR-139-5p Loss-Mediated WTAP Activation Contributes to Hepatocellular Carcinoma Progression by Promoting the Epithelial to Mesenchymal Transition - Liu, Wenli; Gao, Xuewei; Chen, Xiaolong; Zhao, Na; Sun, Ying; Zou, Yawen; Guan, Yize; Yang, Lin; Pei, Xiaoxian; Wang, Guozhen; Wang, Bin; Li, Mingcheng; et al. (Frontiers in Oncology, 2021)
Background: Hepatocellular carcinoma (HCC) is a primary aggressive gastrointestinal neoplasm that affects patients worldwide. It has been shown that Wilms’ tumor 1-associating protein (WTAP) is frequently upregulated in various cancers. However, the potential role of WTAP in HCC remains largely unknown. Methods: The expression levels of WTAP in human HCC tissues were determined by western blotting and immunohistochemical staining. The correlation between WTAP expression, clinicopathological features and HCC prognosis was analyzed. WTAP expression was silenced by shRNA, and the effects of WTAP knockdown on the proliferation and invasion of HCC cells were assessed. The miRNAs involved in the regulation of WTAP expression were identified by bioinformatics analysis and further confirmed by in vitro assays. Results: The WTAP expression levels in liver cancer tissues were significantly elevated compared with those in adjacent normal tissues and significantly correlated with the clinical stage and prognosis of patients with HCC. Further investigation revealed that WTAP knockdown drastically suppressed HCC cell proliferation and invasion abilities. Luciferase reporter assay and validation experiments confirmed that WTAP was a direct target of miR-139-5p. Moreover, the overexpression of WTAP could partly abolish the inhibitory effects of miR-139-5p on HCC cell growth and invasion. Mechanistically, we revealed that the miR-139-5p/WTAP axis regulated HCC progression by controlling the epithelial to mesenchymal transition (EMT). Conclusions: In summary, the results indicate that WTAP is a potential oncogene in HCC and that miR-139-5p negatively regulates WTAP expression. MiR-139-5p/WTAP can be utilized as a potential therapeutic target for HCC.